P3.251 Syphilis and HIV Co-Infection in Patients Atending an AIDS Outpatient Clinic in Vitoria, Brazil. (13th July 2013) - Miranda, A E; Callegari, F M; Neto, L F Pinto; Page, K
Abstract : Background: HIV-positive patients should be regularly screened for syphilis. Detection and treatment of syphilis can help to reduce HIV transmission. Objective: Our goal was to determine the prevalence of and associated factors with syphilis in HIV patients attending an AIDS outpatient clinic in Vitoria, Brazil. Methods: Cross-sectional study was conducted in HIV/AIDS patients. They were interviewed for demographic, behavioural and clinical characteristics and had blood collected (venipuncture and fingertick) for VDRL and treponemal tests (rapid test) after signing an informed consent. Results: A total of 438 patients were included in the study. Over half (55%) of the sample was male, mean age was 43 years (SD±11 years), and mean years of schooling was 8.1 (SD ±4.2 years). The prevalence of syphilis was 5.3%(CI 95% 3.3%–7.3%). The treponemal test was positive in 18.9% of participants. Over one third (37.8%) of the male patients reported a history of sex with men (MSM). No women reported homosexual behaviour. More than two-thirds (70%) of the participants reported consistent condom use in the last year; 6.4% were sexworkers and 25.8% were illicit drug users. A total of 72.4% reported having had one sexual partner in the last year In multivariate analysis, syphilis was associated with male gender [OR = 4.57(CI95%:1.03–20.0]), men who have sex with men [OR = 1.78(IC95%:1.64–4.14)], not on antiretroviral therapy [OR = 0.18(CI 95% 0.06–0.59], and history of previously treated syphilis infection [OR 5.54 (CI95%:1.95–15.76]. Conclusions: Our finding highlights the importance of preventing and promptly treating syphilis in people living with HIV/AIDS. Patients with HIV/AIDS must be screened and monitored annually for early detection of syphilis, to provide early treatment and follow-up to avoid reinfections.